The stratigraphy and structural evolution of the late Proterozoic Gariep belt in the Sendelingsdrif-Annisfontein area, northwestern Cape Province - Von Veh, Mark Wolter (Department of Environmental and Geographical Science, 2016)
Bibliography: pages 128-143.